Cork oak physiological responses to manipulated water availability in a Mediterranean woodland - Besson, Cathy Kurz (2014)
tThis study details the physiological responses of cork oak (Quercus suber L.) to manipulated water inputs.Treatments named as dry, ambient and wet, which received 80, 100 and 120% of the annual precipitation,respectively, were applied to a Mediterranean woodland in southern Portugal. Tree ecophysiology andgrowth were monitored from 2003 to 2005.The impacts of the water manipulation were primarily observed in tree transpiration, especially dur-ing summer drought. Rainfall exclusion reduced the annual stand canopy transpiration by 10% over the2-year study period, while irrigation increased it by 11%. The accumulated tree transpiration matchedprecipitation in spring 2004 and 2005 at the stand level, suggesting that cork oak trees rely on precip-itation water sources during the peak of the growing season. However, during the summer droughts,groundwater was the main water source for trees.Despite the significant differences in soil water content and tree transpiration, no treatment effectscould be detected in leaf water potential and leaf gas exchange, except for a single event after spring irri-gations in the very dry year 2005. These irrigations were intentionally delayed to reduce dry spell durationduring the peak of tree growing season. They resulted in an acute positive physiological response of treesfrom the wet treatment one week after the last irrigation event leading to a 32% raise of stem diame-ter increment the following months. Our results suggest that in a semi-arid environment precipitationchanges in spring (amount and timing) have a stronger impact on cork oak physiology and growth thanan overall change in the total annual precipitation.The extreme drought of 2005 had a negative impact on tree growth. The annual increment of treetrunk diameter in the ambient and dry treatments was reduced, while it increased for trees from the wettreatment. Water shortage also significantly reduced leaf area. The latter dropped by 10.4% in responseto the extreme drought of 2005 in trees from the ambient treatment. The reduction was less pronouncedin trees of the wet treatment (−7.6%), and more pronounced in trees of the dry treatment (−14.7%).Cork oak showed high resiliency to inter-annual precipitation variability. The annual accumulated treetranspiration, the minimum midday leaf water potential and the absolute amount of groundwater used